Benefits management and Information Technology work distribution - Knut Kjetil Holgeid; John Krogstie; Patrick Mikalef; Eirik E. Saur; Dag I. K. Sjøberg (IET Software)
Abstract Organisations spend much money on Information Technology (IT) development and maintenance activities with the intention that these activities will create results that enable benefits for the organisations. This paper seeks to understand potential associations between IT development and maintenance activities and the adoption of benefits management practices to realise value for the organization. The aim is also to uncover potential differences between public and private organisations. We surveyed 86 Norwegian public and private organisations, including data collected in similar surveys every five years since 1993. For the period between 1998 and 2018, we observe a stable pattern of IT work distribution. We found that organisations that managed benefits put more effort into advancing functionality for the end‐users than other organisations, and they realised more benefits. This advantage was particularly true for organisations that managed benefits beyond the early stages of the development lifecycle. Private organisations both managed and realised benefits to a larger extent than public organisations. Our findings can enable organisations to be evidence‐based when choosing management practices to achieve a higher return on investments in IT development and maintenance activities.